Differences in Transforming Growth Factor‐β1/BMP7 Signaling and Venous Fibrosis Contribute to Female Sex Differences in Arteriovenous Fistulas. Issue 16 (18th August 2020) - Cai, Chuanqi; Kilari, Sreenivasulu; Singh, Avishek K.; Zhao, Chenglei; Simeon, Michael L.; Misra, Avanish; Li, Yiqing; Misra, Sanjay
Abstract : Background: Women have decreased hemodialysis arteriovenous fistula (AVF) maturation and patency rates. We determined the mechanisms responsible for the sex‐specific differences in AVF maturation and stenosis formation by performing whole transcriptome RNA sequencing with differential gene expression and pathway analysis, histopathological changes, and in vitro cell culture experiments from male and female smooth muscle cells. Methods and Results: Mice with chronic kidney disease and AVF were used. Outflow veins were evaluated for gene expression, histomorphometric analysis, Doppler ultrasound, immunohistologic analysis, and fibrosis. Primary vascular smooth muscle cells were collected from female and male aorta vessels. In female AVFs, RNA sequencing with real‐time polymerase chain reaction analysis demonstrated a significant decrease in the average gene expression of BMP7 (bone morphogenetic protein 7) and downstream IL17Rb (interleukin 17 receptor b), with increased transforming growth factor‐β1 ( Tgf‐β1) and transforming growth factor‐β receptor 1 ( Tgfβ‐r1) . There was decreased peak velocity, negative vascular remodeling with higher venous fibrosis and an increase in synthetic vascular smooth muscle cell phenotype, decrease in proliferation, and increase in apoptosis in female outflow veins at day 28. In vitro primary vascular smooth muscle cell experiments performed under hypoxic conditions demonstrated, in female compared with male cells, that there was increased gene expression of Tgf‐β1, Tgfβ‐r1, and Col1 with increased migration. Conclusions: In female AVFs, there is decreased gene expression of BMP7 and IL17Rb with increased Tgf‐β1 and Tgfβ‐r1, and the cellular and vascular differences result in venous fibrosis with negative vascular remodeling.